2021
DOI: 10.1021/acs.analchem.0c04682
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Gold Nanoclusters into a Metal–Organic Framework with Efficient Electrochemiluminescence and Their Application for Sensitive Detection of Rutin

Abstract: Ligand-protected gold nanoclusters (Au NCs) are promising electrochemiluminescence (ECL) emitters because of their striking optical properties and excellent biocompatibility, but free vibration and rotation of their ligand result in low ECL efficiency, dramatically limiting their applications. Herein, using the ligand of Au NCs as one of the building units, a Au NC-based metal–organic framework (Au NC-based MOF) was constructed by the coordination-assisted self-assembly strategy, which not only impedes the lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(37 citation statements)
references
References 33 publications
0
37
0
Order By: Relevance
“…Upon coordination-assisted self-assembly, the porous structure of MOFs can not only enhance the electrochemical excitation and reduce the self-quenching effect of AuNCs, but also restrain the energy dissipation triggered by rotation and vibration of ligand to impede nonradiative transition of AuNCs as well. These features endow MOF/AuNCs assemblies with enhanced ECL efficiency which is favorable for ECL sensing [ 72 , 73 ].…”
Section: Electrochemiluminescence (Ecl) Sensingmentioning
confidence: 99%
See 2 more Smart Citations
“…Upon coordination-assisted self-assembly, the porous structure of MOFs can not only enhance the electrochemical excitation and reduce the self-quenching effect of AuNCs, but also restrain the energy dissipation triggered by rotation and vibration of ligand to impede nonradiative transition of AuNCs as well. These features endow MOF/AuNCs assemblies with enhanced ECL efficiency which is favorable for ECL sensing [ 72 , 73 ].…”
Section: Electrochemiluminescence (Ecl) Sensingmentioning
confidence: 99%
“…Yuan et al [ 72 ] first reported the outstanding anodic ECL performance of GSH–AuNCs@ZIF-8 in the presence of coreactant (triethylamine, TEA), where the ECL intensity of GSH–AuNCs@ZIF-8 was increased to nearly ten times that of AuNCs (Fig. 9 ).…”
Section: Electrochemiluminescence (Ecl) Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is adaptable for other NCs with different ligands such as Au 38 (PET) 24 and Au 44 (2,4-DMBT) 26 . In another study, Yuan and co-workers used the ligand of NCs as one of the building units of MOFs to impede the ligand swinging of NCs ( Nie et al., 2021 ). Glutathione (GSH) protected Au NCs (GS-Au NCs) were encapsulated into ZIF-8 to construct the GS-Au NCs@ZIF-8 composite, where Zn 2+ coordinates with both the carboxyl group in the GSH ligand and the nitrogen atom of 2-methylimidazole linkers ( Figure 6 D).…”
Section: Ncs/mof Nanostructures For Catalysismentioning
confidence: 99%
“… (F) Corresponding calibration curve for the rutin determination. Reproduced with permission from Nie et al. (2021) .…”
Section: Ncs/mof Nanostructures For Catalysismentioning
confidence: 99%